Modelling railway bridge degradation based on historical maintenance data - Le, Bryant; Andrews, John (Taylor & Francis, 2016)
As structures deteriorate with age and use, it is necessary to devise a maintenance plan to control their states in a cost effective way. In order to evaluate the effectiveness of alternative maintenance strategies their success must be measured by their ability to control the structure condition. The condition can be expressed for either the entire structure or for the components which make up the structure. A problem is how to express this condition. This is a particular problem for bridges where there can be several deterioration mechanisms taking place and there is no clear way of measuring the current state of either the structure or its elements. One approach to defining the condition of bridges is to use condition scores or condition indices, for the infrastructure owners, as it is desirable that they understand how their population of assets is changing over time. For bridges this has involved providing a condition rating for each structure based on observation and by tracking the changes in the distribution of structure condition for population over time. The current maintenance strategy can then be shown to be inadequate (leading to deteriorating population condition), adequate (producing a stable population condition) or effective and resulting in an improving population condition.